Characterization of the d-Xylulose 5-Phosphate/d-Fructose 6-Phosphate Phosphoketolase Gene (xfp) from Bifidobacterium lactis - Meile, Leo (American Society for Microbiology, 2001)
A d-xylulose 5-phosphate/d-fructose 6-phosphate phosphoketolase (Xfp) from the probiotic Bifidobacterium lactis was purified to homogeneity. The specific activity of the purified enzyme with d-fructose 6-phosphate as a substrate is 4.28 Units per mg of enzyme. K(m) values for d-xylulose 5-phosphate and d-fructose 6-phosphate are 45 and 10 mM, respectively. The native enzyme has a molecular mass of 550,000 Da. The subunit size upon sodium dodecyl sulfate-polyacrylamide gel electrophoresis (90,000 Da) corresponds with the size (92,529 Da) calculated from the amino acid sequence of the isolated gene (named xfp) encoding 825 amino acids. The xfp gene was identified on the chromosome of B. lactis with the help of degenerated nucleotide probes deduced from the common N-terminal amino acid sequence of both the native and denatured enzyme. Comparison of the deduced amino acid sequence of the cloned gene with sequences in public databases revealed high homologies with hypothetical proteins (26 to 55% identity) in 20 microbial genomes. The amino acid sequence derived from the xfp gene contains typical thiamine diphosphate (ThDP) binding sites reported for other ThDP-dependent enzymes. Two truncated putative genes, pta and guaA, were localized adjacent to xfp on the B. lactis chromosome coding for a phosphotransacetylase and a guanosine monophosphate synthetase homologous to products of genes in Mycobacterium tuberculosis. However, xfp is transcribed in B. lactis as a monocistronic operon. It is the first reported and sequenced gene of a phosphoketolase.